Acquired von Willebrand Disease Associated with Monoclonal Gammopathy of Unknown Significance. (1st November 2017) - Basnet, Sijan; Lin, Catherine; Dhital, Rashmi; Mir, Izza; Mohanty, Elan; Tharu, Biswaraj; Ghimire, Sushil; Poudel, Dilli Ram
Abstract : We present a case of a 79-year-old male who presented with retroperitoneal hematoma a week after motor vehicle accident. Prior history and family history of bleeding were nonsignificant. His activated partial thromboplastin time was found to be prolonged in the emergency department. Further workup with coagulation studies showed decreased factor VIII, vWF antigen, and vWF:ristocetin cofactor assay, and negative Bethesda assay, indicating acquired von Willebrand disease. Immunofluorescence to find an underlying etiology was suggestive of MGUS. Management of AvWD depends on controlling active bleeding and treating the underlying cause. He was treated with factor VIII, haemate-p, rituximab, two cycles of IVIg, and three weeks of oral steroids.